2016
DOI: 10.1007/s10753-016-0376-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced Behavioral Alterations Are Alleviated by Sodium Phenylbutyrate via Attenuation of Oxidative Stress and Neuroinflammatory Cascade

Abstract: Oxido-nitrosative stress, neuroinflammation, and reduced level of neurotrophins are implicated in the pathophysiology of anxiety and depressive illness. A few recent studies have revealed the role of endoplasmic reticulum (ER) stress in the pathophysiology of stress and depression. The aim of the present study is to investigate the neuroprotective potential of sodium phenylbutyrate (SPB), an ER stress inhibitor against lipopolysaccharide (LPS)-induced anxiety and depressive-like behavior in Swiss albino mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…Furthermore, a recent report indicated that ER stress can activate NLRP3 inflammasome in macrophage stimulated by pathogen alone in the absence of NLRP3 inflammasome activators [43]. Additionally, increased levels of ER stress makers were observed in the brain after LPS ip injection and relief of ER stress decreased brain cytokine production including IL-1β [57]. Therefore, we investigated a potential role of ER stress in mediating LPS aloneinduced NLRP3-dependent mature IL-1β production in microglia.…”
Section: Er Stress Mediates Lps Alone-induced Nlrp3-dependent Il-1β Pmentioning
confidence: 94%
“…Furthermore, a recent report indicated that ER stress can activate NLRP3 inflammasome in macrophage stimulated by pathogen alone in the absence of NLRP3 inflammasome activators [43]. Additionally, increased levels of ER stress makers were observed in the brain after LPS ip injection and relief of ER stress decreased brain cytokine production including IL-1β [57]. Therefore, we investigated a potential role of ER stress in mediating LPS aloneinduced NLRP3-dependent mature IL-1β production in microglia.…”
Section: Er Stress Mediates Lps Alone-induced Nlrp3-dependent Il-1β Pmentioning
confidence: 94%
“…Each rat was placed at the center of maze with head facing towards the open arm and allowed to freely explore for 5 min. The total number of entries into the open arm, closed arm, and time spent in open arm during the test were recorded and evaluated [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Increasing evidence indicates that the neurotrophic hypothesis of neuropsychiatric disorders is based on the downregulation of brain-derived neurotrophic factor (BDNF) and the neuropeptide VGF (no acronym) expression in the brain [ 16 21 ]. In addition, previous studies have demonstrated that LPS-induced pro-inflammatory cytokine mediate the generation of oxidative parameters [ 9 , 22 ] and the impairment of BDNF [ 23 ] and VGF functions [ 7 ]. Intervening in the process of neuroinflammation along with oxidative stress may be beneficial for the therapy of neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%